Only half of the truth: Managing invasive alien species by rapid assessment. (1st September 2017) - Rohde, Sven; Schupp, Peter J.; Markert, Alexandra; Wehrmann, Achim
Abstract: Marine environments are threatened by biological invaders that are transported via ship hulls or ballast water at increasing rates around the globe. Most management strategies that should prevent or reduce the impact of alien species include prevention and eradication programs that both rely on an early detection of introduced species. Early detection requires an up to date inventory of present species and efficient monitoring programs to identify newly arrived species. This study surveyed potential invasion 'hot spots' in the coastal waters of the central Wadden Sea, including commercial ports ('port' stations) as well as fairways, roads, groynes and oyster reefs ('Wadden Sea' stations) to establish lists of macrobenthic species as baseline for future monitoring. In the ports we applied simultaneously the HELCOM/OSPAR protocol (H/O) and a regional established rapid assessment (RA) to enable the evaluation of the effectiveness and comprehensiveness of both methods. While the RA is mainly based on the visual screening of species in easy accessible habitats in the field, the H/O includes an extensive sampling by operation of scientific divers boat times and a 4-times higher time effort for sample processing. We identified among all sites 273 species including 37 alien species. The fauna was composed of 210 native and 32 alien species, while the flora was composed of 26 native and 5 alien species. The ports were a diverse habitat with species numbers from 65 to 109. At the Wadden Sea stations, exclusively monitored by the less extensive RA, only half of the species numbers (36–66 species) were detected. However, on the oyster reefs the relative occurrence of alien species compared to natives was similar to the ports and one oyster reef (Nordland) even had the highest ratio (25%, 14 species) of alien species of all investigated sites. The H/O protocol identified 179 species compared to 114 species identified by the RA. Regarding alien species, the H/O provided 85% of alien species, the RA only 67%. Especially with regard to the actual discussion on harmonized monitoring protocols within the Northeast Atlantic and Baltic regions, we recommend that future port surveys should apply the more extensive H/O protocol, since restrictions to the RA decrease drastically the chance of an early detection of alien species. We also recommend complementing the survey of ports with natural invasion 'hot spots' like the oyster reefs by rapid assessment. This combined monitoring design secures a significant increase in the early detection of alien species as demonstrated in our study. Highlights: This study surveyed potential invasion hot-spots in the coastal waters of the Wadden Sea, including commercial ports. It used simultaneously a rapid assessment and the HELCOM/OSPAR protocol in ports to enable an evaluation of both methods. H/O provided on average 85% of alien species, the RA only 67%. Future port surveys should apply the more extensive H/O protocol to increase the early detection of alien species. The survey of the ports should be complemented with natural invasion hot-spots like the oyster reefs by rapid assessment.